2015
DOI: 10.1038/nm.3792
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of quartet families with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is genetically heterogeneous, with evidence for hundreds of susceptibility loci. Previous microarray and exome-sequencing studies have examined portions of the genome in simplex families (parents and one ASD-affected child) having presumed sporadic forms of the disorder. We used whole-genome sequencing (WGS) of 85 quartet families (parents and two ASD-affected siblings), consisting of 170 individuals with ASD, to generate a comprehensive data resource encompassing all classes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
412
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 487 publications
(438 citation statements)
references
References 58 publications
16
412
2
8
Order By: Relevance
“…Other studies suggest that mutations in the majority of siblings with ASD are on different genes, again suggesting that siblings share errors in the process of DNA replication and maintenance rather than inheriting a common mutation [60]. One common factor shared with siblings is the prenatal-maternal environment, which is increasingly being recognized as important for developmental outcomes [61].…”
Section: Folate Metabolism: An Example Of Environment-genome Interactionmentioning
confidence: 99%
“…Other studies suggest that mutations in the majority of siblings with ASD are on different genes, again suggesting that siblings share errors in the process of DNA replication and maintenance rather than inheriting a common mutation [60]. One common factor shared with siblings is the prenatal-maternal environment, which is increasingly being recognized as important for developmental outcomes [61].…”
Section: Folate Metabolism: An Example Of Environment-genome Interactionmentioning
confidence: 99%
“…Base calling and analysis were performed using Illumina HiSeq Analysis Software v2‐2.5.55.1311. Reads were mapped to hg19 using Isaac alignment (SAAC00776.15.01.27) and single nucleotide and small indel variants called Isaac variant caller Starling 2.1.4.2 and annotated as previously described4 based on ANNOVAR 5. Copy number variants were detected as described by Trost et al6 Individuals I‐1, I‐2, II‐4, II‐6, II‐8, and II‐9 were also genotyped using Infinium HumanOmni2.5‐8 BeadChip according to the manufacture's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Amazingly, however, there was as much cognitive and language variation within concordant MZ pairs as between pairs, including up to 50 IQ point discrepancy; regression also fails to show concordance in multiplex families (Parr et al, 2011). The opposite problem has also been demonstrated: Yuen et al (2015) did a GWA study of 85 families with two children affected by autism, focusing on genes previously associated with autism. They found that approximately 70% of the sibling pairs did not share an ASD-relevant mutation, but rather had different ones.…”
Section: Genotype-phenotype Relationshipsmentioning
confidence: 99%